HC067047 Ameliorates Sepsis-associated Encephalopathy by Suppressing Endoplasmic Reticulum Stress and Oxidative Stress-Induced Pyroptosis in the Hippocampi of Mice. (1st May 2023) - Zhong, Xiaolin; Wang, Yajuan; Liu, Dandan; Liang, Yue; Liu, WenJia; Huang, Yanmei; Xie, Lihua; Cao, Wenyu; Xu, Yang; Chen, Ling
Highlights: HC067047 treatment suppresses ER stress and oxidative stress in hippocampus of SAE mice. HC067047 treatment inhibits NLRP3 inflammasome-mediated pyroptosis in hippocampus of SAE mice. HC067047 treatment alleviates neuroinflammation and protects the BBB in hippocampus of SAE mice. Abstract: Sepsis-associated encephalopathy (SAE) is a common neurological complication of sepsis and is characterized by hyperneuroinflammation. NLRP3 inflammasome-mediated pyroptosis can induce an inflammatory cascade response and plays a key role in SAE. TRPV4 is involved in the hyperinflammatory response associated with inflammation; however, whether TRPV4 inhibition might alleviate SAE-related brain damage is still unknown. Therefore, we aimed to investigate the role and mechanism of HC067047, a potent inhibitor of TRPV4, in hyperneuroinflammation and blood–brain barrier (BBB) dysfunction in a lipopolysaccharide (LPS)-induced SAE mouse model. We found that HC067047 administration significantly inhibited the expression of TRPV4 and p-CamkIIα in the hippocampi of SAE mice. Furthermore, HC067047 treatment attenuated LPS-induced endoplasmic reticulum (ER) stress and oxidative stress (OS), thus remarkably preventing NLRP3 inflammasome-mediated pyroptosis, as well as the expression of proinflammatory factors (IL-1β and IL-18). Additionally, we found that HC067047 selectively prevented pyroptosis in hippocampal cells, mainly the neurons, oligodendrocytes and the resident microglia. The disruption of BBB integrity in SAE mice was also rescued by HC067047 intervention. Thus, we can conclude that the TRPV4 inhibitor HC067047 could protect against hippocampal cell pyroptosis, which might be due to the attenuation of the NLRP3 inflammasome-mediated pyroptosis pathway caused by ER stress and OS. Our findings suggest a potential preventive role for HC067047 in SAE.